2012
DOI: 10.1016/j.jsbmb.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogenic activity of flavonoid phytochemicals mediated via the c-Jun N-terminal protein kinase pathway. Cell-type specific regulation of estrogen receptor alpha

Abstract: Flavonoid phytochemicals act as both agonists and antagonists of the human estrogen receptors (ERs). While a number of these compounds act by directly binding to the ER, certain phytochemicals, such as the flavonoid compounds chalcone and flavone, elicit antagonistic effects on estrogen signaling independent of direct receptor binding. Here we demonstrate both chalcone and flavone function as cell type-specific selective ER modulators. In MCF-7 breast carcinoma cells chalcone and flavone suppress ERα activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Some of the flavonoids (e.g., genistein, biochanin A, apigenin) acted as antagonists in the ER-bla assay and as agonists in the BG1 ER-luc assay. This behavior may be explained by selective receptor modulator activity33. One aspect of nuclear receptor pharmacology that affects how compounds are assigned active agonist or active antagonist calls results from partial agonist behavior in the assays.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the flavonoids (e.g., genistein, biochanin A, apigenin) acted as antagonists in the ER-bla assay and as agonists in the BG1 ER-luc assay. This behavior may be explained by selective receptor modulator activity33. One aspect of nuclear receptor pharmacology that affects how compounds are assigned active agonist or active antagonist calls results from partial agonist behavior in the assays.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter gene assays were performed as previously described (49,50). MCF-7TN-R cells were plated at 50,000 cells per 24-well plate and allowed to attach overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, accumulating evidence proves that some phytoestrogens exhibit antiestrogenic activity via ER-mediated signaling pathway [16,17,18]. For example, Nakamura et al reported that genistein, an isoflavone found in soy, inhibited proliferation and decreased invasive potential of human osteosarcoma cell line LM8, indicating the role of phytoestrogens in the prevention and treatment of osteosarcomas [19].…”
Section: Discussionmentioning
confidence: 99%